2015
DOI: 10.1002/ejlt.201500025
|View full text |Cite
|
Sign up to set email alerts
|

Infant formula interface and fat source impact on neonatal digestion and gut microbiota

Abstract: Human milk is generally recognized as the gold standard in neonatal nutrition. The structure andcomposition of human milk are better mimicked in infant formulas that include cow s milk lipids andmilk fat membrane extracts, which could also improve physiological properties. Nevertheless, very fewinfant formulas use cow' s milk lipids that are more expensive than vegetable lipids. The potential impactof milk lipid structure and composition on neonatal digestive hydrolysis, intestinal physiology, and gutmicrobiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 78 publications
2
56
0
1
Order By: Relevance
“…At this stage, however, the fact that kinetics of lipid digestion could further modulate plasma TG appearance (Michalski et al, 2006) and b-oxidation rate (Michalski et al, 2005a) was already established in animal models and later on confirmed in human (Vors et al, 2013). In a further study (Oosting et al, 2014), still using a very close design study in mice, it was shown (2015) and Bourlieu et al (2015a).…”
Section: 1mentioning
confidence: 95%
See 4 more Smart Citations
“…At this stage, however, the fact that kinetics of lipid digestion could further modulate plasma TG appearance (Michalski et al, 2006) and b-oxidation rate (Michalski et al, 2005a) was already established in animal models and later on confirmed in human (Vors et al, 2013). In a further study (Oosting et al, 2014), still using a very close design study in mice, it was shown (2015) and Bourlieu et al (2015a).…”
Section: 1mentioning
confidence: 95%
“…These compounds can be added in the IF premix. An important aspect of such addition is not only their protein/phospholipids ratios but also the order of introduction of these two amphiphiles in the emulsion which can impact on the emulsion interfacial composition and structure (Bourlieu et al, 2015a;Gallier et al, 2015). The precise interfacial composition of such biomimetic IF remains to be characterized as well as its susceptibility to digestion.…”
Section: Topical Issuementioning
confidence: 99%
See 3 more Smart Citations